Social media commerce for dummies - Collier, Marsha (--For dummies., 2013)
Traditional advertising and marketing techniques just don't do the job anymore. Today's consumer relies on input from a trusted community when making buying decisions. Learn how to take advantage of their social network channels and interact with them online.